Relative assistance to Australian agriculture and manufacturing since Federation1. (28th August 2014) - Lloyd, Peter; MacLaren, Donald
<x xml:space="preserve">Abstract</x> This paper quantifies the levels of assistance received by producers of the major agricultural crops and animal products in Australia since Federation and compares this with the level of assistance provided to manufacturing producers. First, we construct a series of the production‐weighted average nominal rate of assistance for the whole sector. Then, we compute a measure of the level of assistance received by the Agriculture sector relative to that received by the Manufacturing sector, the Relative Rate of Assistance. Our results show that, from the time of Federation until the 1990s, the economy‐wide pattern of industry assistance discriminated persistently and heavily against the Agriculture sector. The policy of 'protection all round' pursued by the Country/National Party did not prevent this discrimination. In particular, producers of exportables, such as wool and wheat, were heavily discriminated against. Both the intersectoral bias and the differences in assistance among agricultural producers lowered the incomes of the Agriculture sector and the national income.